Realm breaker eaudiobook - Aveyard, Victoria (Realm Breaker, 2021)
Instant #1 New York Times Bestseller! "A true fantasy masterpiece."" —Sabaa Tahir, #1 New York Times bestselling author The Queen of Fantasy strikes again! This stunning new series from Victoria Aveyard, the #1 New York Times bestselling author of the Red Queen series is a high-voltage, high-stakes adventure where kingdoms hang in the balance and betrayal is only a breath away. A strange darkness grows in Allward even Corayne an-Amarat can feel it in her small town at the edge of the sea. The long lost heir to an ancient lineage, it's not until Corayne meets a rag-tag group of companions that she learns how to wield the magic slumbering in her blood—and how together they might stop what's coming. From her seat on the throne, Queen Erida has one aim: build a kingdom worthy of her destiny. While her court hopes to marry her off, Erida will do anything she can to avoid losing her crown—and her freedom. No matter the cost. Meanwhile, shadowy corpse armies march the hillsides and dangerous beasts creep through fissures in the world, and a great evil grows stronger by the day. As the realm descends into chaos, the choices are clear: Save the world...or end it. Realm Breaker is the first book in an epic series, told in multiple-POV chapters that follow an irresistible cast of characters through an incredibly imagined world, with action-packed adventure and lethal twists you won't see coming, perfect for fans of Leigh Bardugo and Tolkien himself. Don't miss Blade Breaker, the #1 New York Times bestselling sequel to Realm Breaker.